Early puberty: a review on its role as a risk factor for metabolic and mental disorders - Sun, Yukun; Liu, Haiyan; Mu, Chunguang; Liu, Peipei; Hao, Changfu; Xin, Yongjuan (Frontiers in Pediatrics, 2024)
Accumulating evidence indicates that there is a trend of early puberty onset in humans. The early timing of puberty has raised concerns due to its association with significant negative health outcomes. However, overall impact and potential risk of early puberty remain uncertain. In this study, we conducted a comprehensive review of existing epidemiological studies to gain insights into the longterm adverse health effects associated with early puberty. Our objective was to provide a consolidated summary of these outcomes at a population level by considering studies that encompass various indicators of puberty. In all, early puberty has been identified as a potential risk factor for various metabolic diseases, such as obesity, diabetes, cardiovascular diseases (CVD). Children who experience early puberty are more likely to have a higher body mass index (BMI) during adulthood, increasing their risk of obesity. Early puberty also has been found to be an independent risk factor for diabetes mellitus, including gestational diabetes mellitus (GDM) and type 2 diabetes mellitus (T2DM), as earlier onset of menarche in girls and voice breaking in boys is associated with a higher prevalence of T2DM. Furthermore, evidence suggests that early puberty may contribute to an elevated risk of CVD, including conditions like coronary heart disease (CHD), stroke, angina, and hypertension. In addition, adolescents who experience early puberty, particularly girls, are more likely to suffer from mental problems, such as behavioral dysfunction and depression. Notably, early puberty has a more significant impact on girls than boys. Further research should consider the underlying mechanisms and potential preventive measures.